Pengaruh Minat terhadap Prestasi Belajar Siswa di Madrasah Ibtidaiyah - Yusi Srihartini (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2021)
The Influence of Learning Interest on Student Achievement at MI Mathla'ul Anwar 05 Cigudeg, Bogor Regency, a survey research with a functional associative quantitative approach. The research aims to: 1) find out the data on the level of interest in learning at MI Mathlaul Anwar 05 Cigudeg, Bogor Regency; 2) find out data on student achievement at MI Mathlaul Anwar 05 Cigudeg, Bogor Regency; 3) determine the effect of interest in learning on student achievement at MI Mathlaul Anwar 05 Cigudeg, Bogor Regency. Research data were collected using questionnaires and documentation techniques. The research instrument used a questionnaire for interest in learning and for student achievement using the general score for Indonesian language subjects. The data analysis technique used a simple linear regression test and the interpretation of the data was carried out in a deductive narrative. The results showed that there was a significant correlation between variable X (interest in learning) and variable Y (student learning achievement) of 0.618. The significance level obtained is 0.000 which is smaller than = 0.050 (one-tailed test), so Ho: = 0 is rejected. Thus, because the significance of 0.000 is smaller than = 0.050 (one-tailed test or one-tailed test), then Ho : = 0 is rejected. This means that there is a significant relationship between interest in learning and student achievement at MI Mafthaul Anwar 05 Cigudeg, Bogor Regency. The form of a simple linear regression equation is obtained = 53.686 + 0.275X. Based on the value of R square, the regression equation can be explained that 38.2% of the variance of student achievement at MI Mafthaul Anwar 05 Cigudeg Bogor Regency can be explained by changes in learning interest. Regression (functional relationship) variable interest in learning with learning achievement statistically with a value of F = 29.635 significant at degrees of freedom k = 1 and n - k - 1 = 48, and P-value = 0.000 which is smaller than = 0.05. Thus, testing the hypothesis Ho:β1=0 against H1: 1≠0 based on the ANOVA table, Ho is rejected because P-value = 0.000 which is smaller than = 0.050. This means that there is a significant effect of interest in learning on student achievement at MI Mafthaul Anwar 05 Cigudeg, Bogor Regency.